Development of the Quality of Teaching Staff at Madrasah Tsanawiyah Al Jam’iyatul-Washliyah 18 Tembung Percut Sei Tuan - Abu Hasan Al-Hasari; Mesiono Mesiono; Muhammad Rifa’i (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Developing the quality of teaching staff is done through good planning, implementing training activities, P3G, workshops, study permits and further studies, evaluating activities that have been implemented and following up on the evaluation results. The purpose of this study is to determine the plans, implementation, evaluation and follow-up that will be carried out by the principal of Madrasah for developing the quality of teaching staff at Madrasah Tsaawiyah Al-Jam'iyatul Washiliyah 18 Tembung Percut Sei Tuan. The method used in this study is qualitative research with descriptive methods. Data collection techniques use interviews, observation and documentation, research data analysis techniques use data collection, data reduction, data presentation and conclusions as well as research data validity checking techniques use source triangulation and technical triangulation. The research location is at Madrasah Tsaawiyah Al-Jam'iyatul Washiliyah 18 Tembung Percut Sei Tuan. The data sources for this research were obtained from the principal of Madrasah Tsaawiyah, the deputy principal of Madrasah Tsaawiyah and the teachers of Madrasah Tsaawiyah Al-Jam'iyatul Washiliyah 18 Tembung Percut Sei Tuan. The results of the study show 1) the plan for developing the quality of educators here looks at the needs that have been determined by the institution, utilizes targets, determines the content of the program, implements activities in the program and finally evaluates the implementation of the program. 2) implements training activities, P3G, workshops, study permits and further studies, evaluates activities that have been implemented and follows up on the results of the evaluation. 3) evaluates the activities implemented. 4). The principal and teachers will continue the programs that have been implemented as usual.